Getting by with a Little Help from Our Friends: The Role of Social Support in Addressing HIV-related Mental Health Disparities among Sexual Minorities in the Lower Rio Grande Valley. Issue 2 (28th January 2021) - Tabler, Jennifer; Mykyta, Laryssa; Schmitz, Rachel M.; Kamimura, Akiko; Martinez, Dora A.; Martinez, Ruben D.; Flores, Paloma; Gonzalez, Karina; Marquez, Alvaro; Marroquin, Gladys; Torres, Andy
ABSTRACT: This study examines how social support and perceived discrimination influence depressive symptoms of sexual minorities (including, lesbian, gay, bisexual-identifying individuals, and others with same-sex sexual partners) relative to heterosexual peers, while considering the role of HIV-positive status. We surveyed low-income, predominantly Hispanic/Latino/as residents receiving STI-testing and/or HIV/AIDS care in the lower Rio Grande Valley of southernmost Texas. Respondents aged 18+ took a self-administered survey in English or Spanish in a clinic waiting room ( N = 273). Based on OLS regression, HIV-positive status (OLS coefficient = 2.54, p < .01) and social support (OLS coefficient = −0.17, p < .001) were significant predictors of depressive symptoms among sexual minorities, but not those who identified as heterosexual. Perceived discrimination was uniquely associated with increased depressive symptoms among sexual minorities (interaction coefficient = 0.21, p < .05). Clinicians treating sexual minority patients for depression should consider developing and applying resources tailored to individuals' level of social support and ongoing experiences of social discrimination.